2015
DOI: 10.1002/jsfa.7149
|View full text |Cite
|
Sign up to set email alerts
|

Integration of life cycle assessment and regional emission information in agricultural systems

Abstract: Results of current LCA studies on agricultural products and systems that do not include REI are under-estimating the life cycle environmental impact. For the LCA of agricultural products and systems, the REI as well as regionalised life cycle inventory data should be developed and integrated into the current LCA approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…For example, spatially explicit simulation models for agricultural nitrogen emissions are available at different complexity, e.g., the complex TNT2 model (Beaujouan et al 2002) or simpler models (EMEP/EEA 2013). Various solutions have been proposed, with some constructed as GIS-based inventory and emission models (Geyer et al 2010, Kim et al 2015. Mutel et al (2012) matched inventory with SCFs by calculating spatial autocorrelation to choose the most appropriate spatial scale of impact assessment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, spatially explicit simulation models for agricultural nitrogen emissions are available at different complexity, e.g., the complex TNT2 model (Beaujouan et al 2002) or simpler models (EMEP/EEA 2013). Various solutions have been proposed, with some constructed as GIS-based inventory and emission models (Geyer et al 2010, Kim et al 2015. Mutel et al (2012) matched inventory with SCFs by calculating spatial autocorrelation to choose the most appropriate spatial scale of impact assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Few of the biofuel LCA studies report on regional impacts (i.e., acidification, eutrophication, smog, water use, etc.) [1,2,8,9], and fewer still take into account the spatial variability of these impacts [8,10]. Regional impacts from biofuel feedstock production could prove to be a substantial issue.…”
Section: Introductionmentioning
confidence: 99%
“…Regional impacts from biofuel feedstock production could prove to be a substantial issue. An LCA study evaluating regional emissions from agricultural systems found that by not including regional emission information, life cycle environmental impacts are likely underestimated [9]. Another study coupling GIS and LCA found variability in changes to regional biodiversity resulting from the production of ethanol from corn and sugar beets, demonstrating the use and importance of spatially located inventory data in LCAs [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation